If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y = x + 4y Solving 5x + 2y = x + 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5x + -1x + 2y = x + -1x + 4y Combine like terms: 5x + -1x = 4x 4x + 2y = x + -1x + 4y Combine like terms: x + -1x = 0 4x + 2y = 0 + 4y 4x + 2y = 4y Add '-2y' to each side of the equation. 4x + 2y + -2y = 4y + -2y Combine like terms: 2y + -2y = 0 4x + 0 = 4y + -2y 4x = 4y + -2y Combine like terms: 4y + -2y = 2y 4x = 2y Divide each side by '4'. x = 0.5y Simplifying x = 0.5y
| -2/n=1.6/11.2 | | 3x-12x-15=15 | | M/-5=-5-18 | | 8x+12+x=180 | | 9r-5r-3r=20 | | 10=s-15 | | -3h-5=22 | | 5/7*2/3= | | 11z-2z+14z+-17z+-12z=12 | | 3x-9/6=4 | | Y=ax+bForx | | 3/4*3/8= | | 8w+12=9 | | 6x-12x-8=-8 | | -3(4z+5)=-15-20+3z | | 6-(3+1)*5=17 | | 3xa+8x-6x+9=2 | | 105=-5(x-10)+15 | | -60+4g=14g | | 84=7(x+7) | | -18z+14z+-20z+8z=16 | | 2x^2=960 | | 28xy^7/32xy^12 | | -6-4=-7a+11 | | -5(-2)+(6(-2)-4)= | | 6-(3*1)+5-1=17 | | -177+5x=23-5x | | 15xcos(55)= | | z=y-m+x | | 4(p+5)+4=10p-1 | | 12=7a | | 8i/3-5i |